A Two‐Dimensional Porphyrin Coordination Supramolecular Network Cathode for High‐Performance Aqueous Dual‐Ion Battery. (10th February 2023) - Tan, Yuanming; Chen, Zhao; Tao, Zengren; Wang, Anding; Lai, Shimei; Yang, Yangyi
Abstract: Iodine has great potential in the energy storage, but high solubility of I3 − has seriously delayed its promotion. Benefited from abundant active sites and the open channel, two‐dimensional coordination supramolecular networks (2D CSNs) is considered to be a candidate for the energy storage. Herein, a 2D porphyrin‐CSN cathode named Zn‐TCPP for aqueous iodine dual‐ion battery (DIB) shows an excellent specific capacity of 278 mAh g −1, and a high energy density of 340 Wh kg −1 at 5 A g −1, as well as a durable cycle performance of 5000 cycles and a high Coulombic efficiency of 98 %. Molecular orbital theory, UV/VIS, Raman spectroscopy and density functional theory (DFT) calculations reveal charge‐transfer interaction between the donor of porphyrin nitrogen and the acceptor of I3 −, and computational fluid dynamics (CFD) simulations demonstrate the contribution of 2D layered network structure of Zn‐TCPP to the penetration of I3 − . Abstract : Via charge‐transfer interaction between porphyrin nitrogen and I3 −, Zn‐TCPP achieves an effective anchoring of I3 − . Besides, the open channels constructed by 2D layered network are beneficial to the penetration of I3 − and the accessibility of the porphyrin nitrogen active sites, which brings an excellent electrochemical performance to the Zn‐TCPP cathode.